Pengembangan Perangkat Pembelajaran Menggunakan Schoology dalam Model Pembelajaran Berbasis Masalah untuk Meningkatkan Motivasi Belajar Peserta Didik - Husnul Sapriani; Mansyur Mansyur; Taty Sulastry (Program Pasca Sarjana UNM, 2019)
This study is a development research, which aims at developing learning tools using Schoology to enhance learning motivation of students on chemical equilibrium subject which is valid, practical and effective to be applied. The development model used in this study referred to Hannafin & Peck’s development model which consisted of need assessment, design, development and implementation. The learning tools using Schoology which had been developed; then, it was validated by two experts. After the validation, the tryout of the learning tools using Schoology was conducted at SMA Negeri 1 Polewali Mandar in grade XI MIPA 4 with the total of 30 students. The result of the study reveals that the learning tools using Schoology development which had been validated shows the mean score of 3.40 which is in valid criteria. The learning tools using Schoology is stated as practical and effective because the practical test which related to: (1) the implementation of learning tools using Schoology is in M = 1.85 in the category of (1.5 ≤ M ≤ 2.0) meaning that the aspect and criteria observed in the implementation of learning tools using Schoology is in entirely implemented category, (2) teachers gave a very positive response on the learning tools using Schoology by 100%, and (3) the students gave a very positive response on the learning tools using Schoology by 85.49%. The learning tools has met effective criteria with the following result: (1) the enhancement of learning motivation of students is from 72.89% to 84.28%, (2) the learning activity of students with the mean score 91.33 is in very active category, and (3) the learning result of students has met effective criteria (≥80%) with the mean percentage of 85.60% which overall is stated as it has met the minimal completeness criteria of the subject.